فعالية استخدام الطريقة الصامتة في تعليم المفردات لدى طلاب الفصل السابع في المدرسة المتوسطة الإسلامية الحكومية ۱ سلوك الجنوبية - أمانة, لطيفة بتري; فبريانتا, ريتا (Asian Journal of Islamic Studies and Da'wah, 2024)
Problem of this research is that there are still many students who stutter in Arabic vocabulary because the vocabulary is too Arabic or the means used by the teacher such and cannot attract students interest this research aims to find out the effectiveness of using the silent way method in teaching vocabulary among the students of the seven semester in the Islamic intermediate school al hukumiyah 1 solok al janubiyah students from the semester a. As the experimental class 30 students in the seventh semester (b) as the control class the research tool used in this research tools used in this research are observation the writers analyzed the data using natural test, homogeneity test and hypothesis test (independent sample test). Research, the researcher decided that the difference is in the degree of the two classes, so that the T of the sap is 2,629 greater than the T of the 5% table is 2,024. And the sig-2 tailed is 58, less than 0,05 the researcher summed up that the nuul hypothesis is rejected and the alternative hypothesis is accepted, meaning that there is an effectivenees of using the silent method in teaching vocabulary among students of the seventh semester 1 islamic intermediate school al-hakamiyah 1 solok al-janubiyah.